Supplying bio-compressed natural gas to the transport industry in Ireland: Is the current regulatory framework facilitating or hindering development?. (1st October 2017) - Goulding, D.; Fitzpatrick, D.; O'Connor, R.; Browne, J.D.; Power, N.M.
Abstract: Compressed Natural Gas (CNG) and biomethane when blended as a transport fuel (bio-CNG) have significant potential in Europe. However, this alternative fuel has not been developed in several European countries. One of the barriers to market penetration is the absence of a coherent regulatory framework to eliminate the disparity between European and national legislation. Using Ireland as a test case, this paper examines how conflicting policies can be aligned to ensure effective bio-CNG market development. A key barrier is the regulatory ambiguity placed on transport fuel suppliers and investors who wish to connect to the network to supply bio-CNG. For example, the Irish 2002 Gas (Interim) (Regulation) Act states that all entities supplying natural gas from the network (including bio-CNG) must hold a supplier licence and are bound by the network code of operations. The obligations of the code act as a potential deterrent to bio-CNG suppliers due to the licencing complexity and associated costs. This paper critiques the current regulatory framework in Ireland, highlights areas of ambiguity and puts forward an aligned solution to allow bio-CNG market participants to utilise the network safely, in a regulatory sound and cost-effective manner. Highlights: The paper reviews the current bio-CNG regulatory legalisation in place in Europe. Develops an efficient bio-CNG regulatory framework in Ireland. The bio-CNG regulatory framework acts a template for other Member States. Determines an economic benefit of €46.6 m for bio-CNG to the Irish Government. Modifies the existing Natural Gas Supply Licence creating a Bio-CNG Supply Licence.